2008
DOI: 10.3748/wjg.14.1097
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transpapillary brush cytology and forceps biopsy in patients with hilar cholangiocarcinoma

Abstract: Brush cytology and forceps biopsy have only limited sensitivity for the diagnosis of malignant hilar tumors. In our eyes, additional diagnostic techniques should be evaluated and should become routine in patients with negative cytological and histological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 29 publications
5
91
1
6
Order By: Relevance
“…Due to its relative ease and safety, many studies have suggested that cytology during ERCP, despite its low sensitivity, remains a good choice for the diagnosis of causes of biliary stricture. [32][33][34][35] To improve the sensitivity, further refinements in technique and procedure have been suggested. One study of cytodiagnosis through ERCP showed that intraductal aspiration had a significantly higher sensitivity (89% versus 78% for adequate samples and 89% versus 37% for all samples) and significantly superior cellular adequacy (92.8% versus 35.7%) than brushing in patients with suspected malignant biliary stricture.…”
Section: Diagnosismentioning
confidence: 99%
“…Due to its relative ease and safety, many studies have suggested that cytology during ERCP, despite its low sensitivity, remains a good choice for the diagnosis of causes of biliary stricture. [32][33][34][35] To improve the sensitivity, further refinements in technique and procedure have been suggested. One study of cytodiagnosis through ERCP showed that intraductal aspiration had a significantly higher sensitivity (89% versus 78% for adequate samples and 89% versus 37% for all samples) and significantly superior cellular adequacy (92.8% versus 35.7%) than brushing in patients with suspected malignant biliary stricture.…”
Section: Diagnosismentioning
confidence: 99%
“…In these published series, the sensitivity of brush cytology and forceps biopsy was evaluated in a heterogeneous patient group with several malignant bile duct strictures. Recently, the diagnostic sensitivity of transpapillary brush cytology and forceps biopsy was evaluated in patients with hilar cholangiocarcinomas [60] . In this series, the sensitivity of transpapillary brush cytology was 41.4% and the sensitivity of forceps biopsy was 53.4%.…”
Section: Brush Cytology and Forceps Biopsymentioning
confidence: 99%
“…Biliary brushing cytology, although highly specific, has suffered from low to moderate sensitivity (15%Ϫ68%). [2][3][4][5][6] As a result, ancillary diagnostic techniques including mutation analysis, [7][8][9][10][11] DNA ploidy analysis, 12,13 methylation analysis, 14 -17 and fluorescence in situ hybridization (FISH), 2,4,18,19 have been studied to improve tumor detection.…”
mentioning
confidence: 99%